Systematic Review: Analisis Pendekatan Kecerdasan Majemuk pada Pembelajaran Fisika SMA (Universitas Negeri Surabaya, 2023)
This study aims to analyze the approach of compound intelligence to learning physics in SMA. This type of research is library research using the PRISMA method, which is carried out systematically and follows research protocols. The data collection technique used in this study uses the PRISMA method to segregate data into articles from the last ten years (2012–2021) on Google Scholar and Crossref. The stages carried out include identification, screening, and inclusion. At the identification stage, use the keyword